2020
DOI: 10.1101/2020.07.10.189118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interest of circulating tumor DNA as a biomarker for canine cancers: illustration in histiocytic sarcoma, oral malignant melanoma and multicentric lymphoma

Abstract: Circulating tumor DNA (ctDNA) has become an attractive biomarker in human oncology and may be informative in cancer-affected dogs. By performing ddPCR or PARR methods, we detected tumor-specific point mutations, copy number alterations and chromosomal rearrangements in the plasma of cancer-affected dogs. It allowed the detection of ctDNA in 2/8 (25%) oral malignant melanoma cases, 12/13 (92.3%) lymphoma cases and 21/23 (91.3%) histiocytic sarcoma (HS) cases. The value of ctDNA to diagnose HS was explored in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The molecular basis of the relationship between tumor burden and cfDNA levels was identified in this study. Moreover, an increase in cfDNA levels was observed 42 days before clinical relapse (e.g., an increase in lymph node size), confirming the potential of cfDNA measurements for monitoring tumor relapse ( 18 ). However, in our study, dogs no.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The molecular basis of the relationship between tumor burden and cfDNA levels was identified in this study. Moreover, an increase in cfDNA levels was observed 42 days before clinical relapse (e.g., an increase in lymph node size), confirming the potential of cfDNA measurements for monitoring tumor relapse ( 18 ). However, in our study, dogs no.…”
Section: Discussionsupporting
confidence: 55%
“…A significant discovery of our study is the correlation between the sum of LD and the cfDNA level of dogs with multicentric lymphoma; thus, continual monitoring of plasma cfDNA concentrations might be useful to assess the response to chemotherapy in patients with multicentric lymphoma. A recent study confirmed the correlation between cfDNA fraction (% of total plasma cfDNA) obtained through PCR for antigen receptor rearrangement ( 18 ) and the sum of LD during chemotherapy in four dogs with high-grade B -cell multicentric lymphoma. The molecular basis of the relationship between tumor burden and cfDNA levels was identified in this study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Published research on canine cfDNA has covered a variety of clinical applications, including trauma, sepsis, thromboembolism, and neoplasia, and has focused primarily on determining the concentration of cfDNA in plasma as correlated to a particular clinical state or as a predictor for certain clinical outcomes ( 84 , 148 151 , 167 , 169 , 191 203 ). Studies that evaluated cfDNA concentrations in healthy canine subjects have reported median concentrations ranging from less than 1 ng/mL to greater than 500 ng/mL ( 148 , 149 , 167 , 169 , 194 203 )—significantly wider than the range documented in healthy humans (typically 0–20 ng/mL) ( 204 ). These wide-ranging findings suggest that additional research employing well-controlled, large-scale studies is required to better understand the fundamental characteristics of cfDNA in dogs; they also point to the need for standardized, reproducible methods for blood collection, extraction, and measurement of canine cfDNA.…”
Section: Liquid Biopsy: the Next Frontier In Veterinary Cancer Carementioning
confidence: 99%